ACETYLCHOLINESTERASE INHIBITORY ACTIVITY OF SOME VEGETABLES AND ISOLATION OF THE ACTIVE CONSTITUENTS FROM SELECTED PLANT - Cut Nuria, Maulita
Dementia is a global health problem that requires serious treatment. Statistical data in 2015 estimated about 46.8 million people in the world were living with dementia. Generally, dementia affects elderly population. The Indonesian Ministry of Health estimates the number of elderly to be around 27.08 million in 2020. Alzheimer’s disease is a disease that is characterized by dementia, which is associated with decreased of neurotransmitter acetylcholine. The main cause of Alzheimer's disease is not known certainly. The disease is associated with several factors including genetic, viral infections, and inadequate diet. One of the means to improve memory is to increase acetylcholine by inhibiting the acetylcholinesterase enzyme (AChE). Inhibitor AChE compounds can be obtained from plants and people who consume vegetables every day can reduce the risk of dementia. The purpose of this study was to investigate the AChE inhibitory activity of 18 vegetables that are widely used by Indonesian Sundanese and Javanese ethnics groups. Many research studies showed that compounds originating from nature such as alkaloid, phenolic and flavonoid compounds could be used to treat neurodegenerative diseases. In this study, qualitative phytochemical screening of extracts and quantitative determination of total phenolic and flavonoid content of the extract were conducted. Potential fraction of the selected plant was further investigated for the chemical ingredient. The structure of compounds isolated from potential fraction were determined and the IC50 of AChE inhibition were calculated. The inhibitory activity of extracts, fractions, and isolates against AChE was carried out in vitro by Ellman’s colorimetric method. Phytochemical screening was carried out on triterpenoid/steroid, alkaloid, phenolic, flavonoid, saponin and tannin compounds. Analysis of total phenolic content was carried out by the Folin- Ciocalteu method, meanwhile total flavonoid content was determined using aluminum chloride. The stages of isolation were extraction, fractionation, separation, purification, and characterization. Extraction was done by maceration using 95% ethanol. The determination of potential extracts was done by determining the extracts that had IC50 values of less than 1000 µg/ml. The potential iv extracts was partitioned using n-hexane, ethyl acetate, methanol, 70% methanol and water, respectively. The determination of the potential fraction was done by selecting the fraction that had the smallest IC50 value and relatively high yield. Separation and purification of compounds in the potential fraction were carried out by Vacuum Liquid Chromatography (VLC), followed by preparative High- Performance Liquid Chromatography (HPLC) and preparative reverse phase Thin Layer Chromatography (TLC). The characterization of isolates was carried out by the UV-Vis spectrophotometry, mass spectrometry and NMR spectrometry. Structure elucidation was based on data derived from the characterization results. The results showed there were 12 plant species that inhibited the activity of AChE, while 6 plant species had no activity when tested in the concentration used. This activity has never been reported before. Plant extracts that had IC50 values of less than 1000 µg/mL (potential extracts) were Cosmos caudatus, Manihot esculenta, Ocimum americanum, and Psophocarpus tetragonolobus. Phytochemical screening showed that all of the extracts contained phenolic and flavonoid compounds. Total phenolic and flavonoid contents of the four potential extracts were also greater than other extracts. The potential fraction of plants which was further investigated was the methanol soluble fraction of cassava leaf (MSFC). Isolation results from selected plants obtained two flavonoid glycoside compounds whose structures were determined as kaempferol-3-O-rutinoside (nicotiflorin) and quercetin-3-O-rutinoside (rutin). Both of these compounds had AChE inhibitory activity with IC50 values of nicotiflorin were 310.2 ± 7.1 ?g/mL and IC50 values of rutin could not be determined until the highest concentration tested (500 ?g/mL). This research provides evidence of the potential of ethanol extracts of C. caudatus, M. esculenta, O. americanum and P. tetragonolobus as AChE inhibitors. These extracts had relatively high contents of total phenolic and flavonoid, which might be responsible for the AChE activity. The active compounds such as flavonoids were a source of natural products and could be used as an AChE inhibitor.